RNAi-Mediated Silencing of Pgants Shows Core 1 O-Glycans Are Required for Pupation in Tribolium castaneum - Li, Weidong; De Schutter, Kristof; Van Damme, Els J. M.; Smagghe, Guy (Frontiers in Physiology, 2021)
Protein glycosylation is one of the most common and most important post-translational modifications. Despite the growing knowledge on N-glycosylation, the research on O-glycosylation is lagging behind. This study investigates the importance of O-glycosylation in the post-embryonic development of insects using the red flour beetle, Tribolium castaneum, as a model. We identified 28 O-glycosylation-related genes (OGRG) in the genome of the red flour beetle. Based on their position in the O-glycosylation pathways, the abundance of the O-glycans they synthesize and functional studies in Drosophila melanogaster, 14 OGRGs were selected for functional analysis. The expression profile of these OGRGs was mapped throughout the developmental stages of the insect and in the different tissues of the pupa and adult. Subsequently, these genes were silenced using RNA interference (RNAi) to analyze their role in development. A broad spectrum of phenotypes was observed: from subtle effects and disrupted wing formation when silencing the genes involved in O-mannosylation, to blockage of pupation and high mortality after silencing of the genes involved in O-GalNAc and core 1 O-glycan (O-GalNAc-Gal) synthesis. RNAi experiments were also performed to assess the effects of blocking multiple pathways of O-glycosylation. However, the observed phenotypes were similar to those of the single gene RNAi experiments. All these results indicate the importance of O-glycosylation for successful post-embryonic development in T. castaneum.